Urinary dysfunction in patients with vascular cognitive impairment - Zhao, Panpan; Zhang, Guimei; Shen, Yanxin; Wang, Yongchun; Shi, Lin; Wang, Zicheng; Wei, Chunxiao; Zhai, Weijie; Sun, Li (Frontiers in Aging Neuroscience, 2023)
Vascular cognitive impairment (VCI) is caused by vascular pathologies, with the spectrum of cognitive disorders ranging from subjective cognitive dysfunction to dementia. Particularly among older adults, cognitive impairment is often complicated with urinary dysfunction (UD); some patients may present with UD before cognitive impairment owing to stroke or even when there are white matter hyperintensities on imaging studies. Patients with cognitive impairment often have both language and movement dysfunction, and thus, UD in patients with VCI can often be underdiagnosed and remain untreated. UD has an impact on the quality of life of patients and caregivers, often leading to poor outcomes. Medical history is an important aspect and should be taken from both patients and their caregivers. Clinical assessment including urinalysis, voiding diary, scales on UD and cognitive impairment, post-void residual volume measurement, uroflowmetry, and (video-) urodynamics should be performed according to indication. Although studies on UD with VCI are few, most of them show that an overactive bladder (OAB) is the most common UD type, and urinary incontinence is the most common symptom. Normal urine storage and micturition in a specific environment are complex processes that require a sophisticated neural network. Although there are many studies on the brain–urinary circuit, the specific circuit involving VCI and UD remains unclear. Currently, there is no disease-modifying pharmacological treatment for cognitive impairment, and anti-acetylcholine drugs, which are commonly used to treat OAB, may cause cognitive impairment, leading to a vicious circle. Therefore, it is important to understand the complex interaction between UD and VCI and formulate individualized treatment plans. This review provides an overview of research advances in clinical features, imaging and pathological characteristics, and treatment options of UD in patients with VCI to increase subject awareness, facilitate research, and improve diagnosis and treatment rates.